Studying and Analyzing the Performance Efficiency of the Cranes at the Container Berths in the Port of Umm Qasr by Using Queuing Theory - AL-Hassany, Marwan (The Gulf Economist, 2023)
The current research aims to study and analyze the efficiency of the performance of quay cranes at container terminals, which is one of the most important logistical activities (container handling) at container terminals. This can be done by using one of the mathematical models of the theory of parallel queues, and determining the optimal number of service channels (the number of quay cranes). It works on balancing the costs of waiting and service and reducing the total cost, reducing waiting times, and increasing the rate of service activity, which ultimately leads to enhancing the competitive advantage. The research relied on the mixed approach, and also relied on the case study strategy by conducting the study on one of the container terminals in the port of Umm Qasr, which is (the multi-purpose terminal of Basra). The data for the study was collected through field visits and interviews with those in charge of managing the logistics activities at the port. The collected data included recording the arrival times of transport trucks to the service channels represented by quay cranes, in order to apply the mathematical models to queuing theory. The research reached number of conclusions, the most important one was that the process of allocating cranes doesn’t fit with the efficiency of the cranes after measuring the performance of quay cranes operating in the container terminal specified for the study. Recommendations presented at the end of the current research.